Years of potential life lost in pre-diabetes and diabetes mellitus: data from a 40-year follow-up of the Israel study on Glucose intolerance, Obesity and Hypertension - Micha Rapoport; Angela Chetrit; Dror Cantrell; Ilya Novikov; Jesse Roth; Rachel Dankner (BMJ Open Diabetes Research & Care, 2021)
Introduction We examined years of potential life lost (YPLL) associated with pre-diabetes as compared with either normoglycemia or diabetes, using data of the Israel cohort of Glucose intolerance, Obesity and Hypertension 40-year follow-up.Research design and methods Men and women (N=2844, mean age 52.0±8.2 years) who underwent oral glucose tolerance test and anthropometric measurements, during 1976–1982, were followed for mortality until May 2019. Multiple imputation procedures for missing mortality dates and multivariable regression mixed models were applied.Results At baseline, 35.8%, 48.8% and 15.4% individuals were found with normoglycemia, pre-diabetes, and diabetes, respectively. The average difference in YPLL associated with pre-diabetes as compared with normoglycemia was 4.3 years (95% CI 3.3 to 5.2; p<0.001). YPLL were 1 year higher in women with pre-diabetes than in men with pre-diabetes. These differences persisted mainly in individuals younger than 60 years, and those with body mass index (BMI) <25 kg/m2, at baseline. Adjusting for age, sex, country of origin, smoking status, BMI, and blood pressure, the average difference in YPLL associated with pre-diabetes as compared with normoglycemia was 2.0 years (95% CI 1.2 to 2.8; p<0.001). Significant reductions of 5.9 years (95% CI 4.8 to 7.0) on average were observed for diabetes as compared with pre-diabetes and 7.9 years (95% CI 6.7 to 9.1) as compared with individuals with normoglycemia.Conclusions This study reveals that life expectancy of middle-aged individuals with pre-diabetes is shorter than of normoglycemic ones. These findings are especially relevant in view of the rising worldwide prevalence of pre-diabetes within younger age groups and underscore the crucial importance of interventions by either lifestyle modification or drug therapy capable of delaying progression from pre-diabetes to diabetes to reduce the YPLL in this high-risk group.